Absence of nonhematopoietic MHC class II expression protects mice from experimental autoimmune myocarditis. Issue 3 (22nd December 2015) - Thelemann, Christoph; Haller, Sergio; Blyszczuk, Przemyslaw; Kania, Gabriela; Rosa, Muriel; Eriksson, Urs; Rotman, Samuel; Reith, Walter; Acha‐Orbea, Hans
Abstract : A transgenic mouse strain that lacks inflammation‐induced MHCII expression by nonhematopoietic cells is resistant to experimental autoimmune myocarditis, while immune‐competent control mice develop cardiac pathology accompanied by cardiac endothelial MHCII expression. These results suggest a role for cardiac endothelial MHCII expression to contribute to cardiac pathology during myocarditis. Abstract : Experimental autoimmune myocarditis (EAM) is a CD4 + T‐cell‐mediated model of human inflammatory dilated cardiomyopathies. Heart‐specific CD4 + T‐cell activation is dependent on autoantigens presented by MHC class II (MHCII) molecules expressed on professional APCs. In this study, we addressed the role of inflammation‐induced MHCII expression by cardiac nonhematopoietic cells on EAM development. EAM was induced in susceptible mice lacking inducible expression of MHCII molecules on all nonhematopoietic cells (pIV−/− K14 class II transactivator (CIITA) transgenic (Tg) mice) by immunization with α‐myosin heavy chain peptide in CFA. Lack of inducible nonhematopoietic MHCII expression in pIV−/− K14 CIITA Tg mice conferred EAM resistance. In contrast, cardiac pathology was induced in WT and heterozygous mice, and correlated with elevated cardiac endothelial MHCII expression. Control mice with myocarditis displayed an increase in infiltrating CD4 + T cells and in expression of IFN‐γ, which is the major driver of nonhematopoietic MHCII expression. Mechanistically, IFN‐γ neutralization in WT mice shortly before disease onset resulted in reduced cardiac MHCII expression and pathology. These findings reveal a previously overlooked contribution of IFN‐γ to induce endothelial MHCII expression in the heart and to progress cardiac pathology during myocarditis.